Review—Opportunities for Rapid, Sensitive Detection of Troponin and Cerebral Spinal Fluid Using Semiconductor Sensors. Issue 3 (20th November 2019) - Carey, Patrick H.; Lobo, Brian C.; Gebhard, Michael P.; Leon, Marino E.; Flax, Sherri D.; Harris, Neil S.; Liao, Yu-Te; Chang, Chin-Wei; Lin, Jenshan; Ren, Fan; Pearton, S. J.
Abstract : There are opportunities for development of modularized, inexpensive protein biomarker sensors in clinical applications. In this review we focus on two of these, namely early diagnosis of acute myocardial infarction (AMI) and detection of cerebral spinal fluid (CSF). Evaluation of patients with acute chest pain is challenging due to the heterogeneity of the underlying conditions, leading to patients with AMI being mistakenly sent home from emergency rooms or those at low risk for an adverse cardiac event being unnecessarily admitted without precise cardiac biomarker testing. Cardiac troponin I (cTnI) in cardiac muscle tissue is a standard clinical biomarker for AMI, as its concentration rises quickly in the blood during release from myocardial cells following cell death. The time-dependence of the cTnI concentration is the basis of antigen-antibody methodologies such as radioimmunoassay and enzyme-linked immunosorbent assay (ELISA). These methods are time consuming, leading to delays in diagnosis and higher costs. The challenge is to develop a real-time, accurate, low-cost point-of-care heart attack sensor. The coefficient of variation must be precise, within the parameters established by the American College of Cardiology. Similarly, leakage of cerebrospinal fluid (CSF) is a critical condition with a high risk of meningitis and potential mortality. The primary methods of detection for the biomarker β2-Transfferin (B2T) are immunofixation electrophoresis (IFE) and ELISA. Consistent IFE results down to 2 μg/mL can be obtained in patient samples, but requires a minimum 2.5-hour testing period, which is not expedient for real time feedback during surgery in or around the central nervous system. Additionally, to achieve good sensitivity and handle the inherently low concentration of B2T in CSF, lab procedures require samples to be concentrated or run in duplicate to ensure accurate detection. Real time turnaround is on the order of days. To alleviate the slow turn-around times, there is strong interest in electronic detection methods for proteins using biologically functionalized transistors, which provide an electronic readout and are readily integrated with wireless data transmission.